MANUFACTURE AND USE OF GUNPOWDER IN SHAMIL’S STATE - Dadaev, U U; Tilakaeva, H O (History, Archeology and Ethnography of the Caucasus, 2016)
The article deals with the study of an important and interesting problem of manufacture and use of gunpowder in Shamil’s state. The authors of the article specify the major deposits of sulfur and saltpeter, which were required to produce gunpowder, and consider the problems of construction of gunpowder factories in the state Imamate. To date, the problem is little-studied. There are various sources concerning the problem: recollections of eyewitnesses and participants of these events, Imam’s letters to his naibs. Taking into account the available data, the problem should be studied in great detail.